Hepatoprotective Effect of Solanum melongena/Eggplant against Acute Hepatitis - Nabhan Komara; Herri S. Sastramihardja; Afiati Afiati (Althea Medical Journal, 2015)
Background: Hepatitis is a liver inflammation that can be acute or chronic and may cause damage to hepatocytes such as necrosis.. Hepatocyte necrosis can be inhibited by antioxidants such as flavonoids found in Solanum melongena fruit. This study aimed to determine the hepatoprotective effect of Solanum melongena fruit infusion to inhibit hepatocytes damage in CCl4-induced rats.Methods: Twenty five male Wistar rats were randomly divided into five groups, and adapted for 7 days before the experimental study. Negative and positive groups were given aquadest, Group III−V were given Solanum melongena fruit infusion containing 1.125 grams, 2.25 grams and 4.5 grams orally for 9 days. At the 9th day, all rats were induced by 8 mL/kgBW of 10% CCl4 in paraffin, except for the negative group. Rats were sacrificed on the 11th day, and liver biopsy preparations were made. Hepatocyte necrosis was counted and was analyzed by Kruskal-Wallis test and Mann-Whitney test. Results: The study showed that the percentage of necrotic hepatocytes in group III, IV a nd V were lower than in the positive group. Using Mann-Whitney test, there were significant differences in negative group, group III, and group V (p<0.05). Meanwhile, unsignificant difference was seen between the positive group and group IV (p>0.05). Kruskal-Wallis test showed that there weresignificantly differences among groups (p<0.05). Conclusions: Solanum melongena fruit infusion has hepatoprotective effects against acute hepatitis in rat model histopathologically.Keywords: CCl4, flavonoids, hepatocyte, necrosis, Solanum melongena DOI: 10.15850/amj.v2n1.434